Inclusiveness in Higher Education: Key Ideas, Challenges and Barriers - Nataliya Dub (Pedagogical Discourse, 2024)
The idea of inclusiveness in the educational practice of training future specialists in Ukraine gained popularity only at the beginning of the 21st century. It is still at the stage of conceptual, regulatory and institutional consolidation. The need to transform higher education in the direction of implementing the principles of inclusion is caused by global changes in Ukrainian society, which initiate its humanization and large-scale integration of leading scientific achievements into educational practice. The integration of «special» students into higher education institutions is a natural stage in the development of the higher education system of Ukraine, which declares equal opportunities for all students to obtain an education. Inclusive education is an integrative unit of social space, which consists of a set of system structural components and blocks that determine the specifics of its content. The content of education within the scope of inclusion is implemented in a format accessible to each participant. The study of the essence of the inclusive educational environment of higher education institutions made it possible to assume that it has both general characteristics: organization, length in time and space, content and structure, and specific ones: accessibility, polysubjectivity, barrier-free, variability (content, temporal, organizational). The set of barriers that students with special needs face when enrolling in higher education institutions (physical, spatial, informational, communicative, etc.) is specified. It is emphasized that the effective implementation of inclusive education is possible under the conditions of social understanding of disability, where awareness of the problems of physical health of a person depends on the level of development of society. It is determined that the introduction of inclusive education into the higher education system should become a long-term strategy for its transformation. The vector of inclusiveness should implement a systemic approach to the organization of the educational process, in which various subjects participate. Their actions should be based on interaction, cooperation, mutual understanding, which will ultimately contribute to improving the quality and efficiency of the educational process. In general, inclusion in higher education is interpreted as a specially organized system of spatial, material and technical, educational and methodological means of learning, which covers a set of interdependent processes and allows each student (normotypical and with special educational needs) to take full part in the educational process of higher education.